Sleeve Gastrectomy-Induced AMPK Activation Attenuates Diabetic Cardiomyopathy by Maintaining Mitochondrial Homeostasis via NR4A1 Suppression in Rats - Li, Songhan; Dong, Shuohui; Xu, Qian; Shi, Bowen; Li, Linchuan; Zhang, Wenjie; Zhu, Jiankang; Cheng, Yugang; Zhang, Guangyong; Zhong, Mingwei (Frontiers in Physiology, 2022)
Diabetic cardiomyopathy (DCM) is characterized by impaired diastolic and systolic myocardial performance and is a major cause of morbidity and mortality in patients with diabetes. Surgical bariatric procedures, such as sleeve gastrectomy (SG), result in remission of type 2 diabetes (T2DM) and have benefits with myocardial function. Maintaining cardiac mitochondrial homeostasis is a promising therapeutic strategy for DCM. However, whether SG surgery affects mitochondrial function and its underlying mechanism remains unclear. This study aimed to investigate the effect of SG surgery on mitochondrial homeostasis and intracellular oxidative stress in rats with DCM. We also examined cellular phenotypes and molecular mechanisms in high glucose and high fat-stimulated myocytes. The rat model of DCM was established by high-fat diet feeding and low-dose streptozotocin injection. We observed a remarkably metabolic benefit of SG, including a reduced body weight, food intake, and blood glucose levels, and restored glucose tolerance and insulin sensitivity postoperatively. Also, SG ameliorated the pathological cardiac hypertrophy, myocardial fibrosis and the dysfunction of myocardial contraction and diastole, consequently delayed the progression of DCM. Also, SG restored the mitochondrial dysfunction and fragmentation through the AMPK signaling activation mediated NR4A1/DRP1 suppression in vivo. H9c2 cardiomyocytes showed that agitation of AMPK could reverse the mitochondrial dysfunction somehow. Collectively, our study provided evidence that SG surgery could alleviate mitochondrial dysfunction in DCM. Moreover, AMPK-activated NR4A1/DRP1 repression might act as a significant reason for maintaining mitochondrial homeostasis in the myocardium, thus contributing to morphological and functional alleviation of DCM.